Robotics Teaching and Tools to Promote Better Didactic in Public High-Schools - Moreira, Mariana; Baptista, Roberto; Oliveira, Caio; Bernardes, Mariana (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Robotics has taken a prominent place in the classroom. However, each class has different reactions, makeup, and backdrops. In this work, it is proposed that the literature findings are as crucial as in-class experience and insights. Based on Constructivism and Constructionism, it is suggested that evaluation methods can lead to course improvement and student motivation rather than actual in-cross comparisons between peers. It is also indicated that the presence of girls in STEAM is related to a social construct, instead of less affinity.